Experiment Evaluation on the Porosity of Plasma Coating from Ceramic Al2O3 – TiO2 Using the Metallography - vu, duong; Hung , Ha Minh (Universitas Ahmad Dahlan, 2024)
Background: The objective of this paper is an experimental investigation of the metallographic porosity of plasma coating using standard materials from the ceramic system Al2O3-TiO2 on the substrate of steel SS400 at laboratory scale Lab at the Research Institute of Mechanical Engineering. Contribution: The main contribution of the research is the evaluation of the porosity of the coating under the influence of the main technological parameters since the porosity plays a significant role in the performance of the working surface using the built-in Image Pro-Analyzer software in the Axiovert 25 MAT microscope. Method: The spraying material is Al2O3-TiO2 powder. The input parameters are: spraying distance (Lp; current of plasma stream (Ip); powder feed flow (Gp and spraying rate (Vp). Results: The findings show that the average porosity of the Al2O3-TiO2 plasma coating is inversely decreasing in the increasing direction of the distance: spray in the range Lp = 100–200 mm, increase proportional to the increase of the current plasma flow rate in the range Ip = 400–600 A, provided that the powder feed flow Gp = 1.7 kg/h and the spraying rate Vp = 50 mm/min. Conclusion: The degree of influence of the three main technological parameters (Lp, Ip, and Gp) in the survey limit domain may be due to the selected Lp spray distance within the relatively wide recommended range of the plasma spraying equipment supplier. It is recommended to conduct the experimental planning of the L27 type to localize the optimum area.